Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Quick on the Draw terhadap Keaktifan Belajar pada Pembelajaran PAI-BP Kelas VIII di SMP Negeri 1 Sungai Pua - Melati, Rima; Arifmiboy, Arifmiboy; Ilmi, Darul; Afrinaldi, Afrinaldi (Lembaga Yasin AlSys, 2024)
This research is motivated by the fact that students' learning activity is still relatively low. The aim is to find out whether the average learning activity of participants is above 75 and whether there is a significant influence on PAI-BP class VIII learning on the subject matter